Cucumber tolerance to glufosinate applied preplant or preemergence. (9th June 2022) - Randell, Taylor M.; Vance, Jenna C.; Hand, Lavesta C.; Grey, Timothy L.; Culpepper, A. Stanley
Abstract: Georgia vegetable growers produce more than 27% of the nation's fresh-market cucumbers. To maximize yields and profit, fields must be weed-free when planting. Limitations with current burndown herbicide options motivated academic, industry, and U.S. Department of Agriculture partners to search for new tools to assist growers. One possibility, glufosinate, controls many common and troublesome weeds, but its influence on cucumber development through residual activity when applied before or at planting is not understood. Thus, four different studies were each conducted two to four times from 2017 to 2020 to determine 1) transplant cucumber response to preplant glufosinate applications as influenced by rate, overhead irrigation, and interval between application and planting; and 2) seeded cucumber response to preemergence (PRE) glufosinate applications as influenced by rate, overhead irrigation, and planting depth. Glufosinate applied at 330, 660, 980, and 1, 640 g ai ha −1 the day before transplanting caused 11% to 53% injury on sandy, low organic matter soils. Cucumber vine lengths and plant biomass were reduced up to 28% and 46%, respectively, with the three highest rates. Early-season yield (harvests 1 to 4) noted a 31% to 60% yield loss with glufosinate at 660 to 1, 640 g ha −1 with similar trends observed with total yield (11 to 13 harvests). Irrigation (0.75 cm) after application and before transplanting reduced injury to less than 21%, eliminated vine length and biomass suppression except at the highest rate, and eliminated yield loss. Extending the interval between glufosinate application and transplanting from 1 to 4 d was not beneficial, and further extending the interval to 7 d significantly reduced injury half the time. When applied PRE to seeded cucumber and combining the data across locations, glufosinate caused less than 7% injury even at 1, 640 g ha −1 . Seeded plant vine lengths, biomass, and marketable yield were not influenced by the PRE application, and neither irrigation nor planting depth influenced seeded crop response to glufosinate.